Reinforcement learning in non-stationary environments using spatiotemporal analysis - Göncü, Burak Muhammed (My University, 2017)
Geleneksel pekiştirmeli öğrenme (PÖ) yöntemleri ortamın veya hedefin değişkenlik gösterdiği durumlarda öğrenme sağlayamamaktadırlar. ABSTRACT Traditional reinforcement learning (RL) approaches fail to learn a policy to attain a dynamic or non-stationary goal.
Keywords: Bilgisayar, Mühendislik; durağan olmayan RL; Non-stationary; pekiştirmeli öğrenme; RL